Influencing Tax Compliance Through Awareness: Evidence from Indonesian E-commerce Entrepreneurs - Heru Nur Akhmad (Journal Of Economic Cluster, 2025)
This study aims to analyze the influence of Taxpayer Awareness on Tax Compliance among Shopee e-commerce entrepreneurs in South Tangerang City. A quantitative approach was employed, with data collected from 96 respondents selected through non-probability sampling based on the Lemeshow formula. Data were analyzed using linear regression, t-test, and the coefficient of determination (R2). The results indicate that Taxpayer Awareness has a positive and significant effect on Tax Compliance. The R2 value of 0.823 suggests that Taxpayer Awareness accounts for 82.3% of the variation in tax compliance. Practically, these findings imply that policies to increase tax revenue in the digital economy sector should prioritize persuasive educational programs and simplified access to tax information rather than relying solely on strict enforcement. Furthermore, strategic collaboration with e-commerce platforms to integrate tax reminder features could assist platform management in fostering a legally compliant business ecosystem. The study concludes that strengthening individual awareness is the primary key to optimizing tax collection within the e-commerce sector.